The seven paths changing one's way of walking in the world - Good Buffalo Eagle (San Francisco : Berrett-Koehler Publishers, 2013)
"Too many people today have taken the wrong path. They walk alone, seeking peace and fulfillment in isolation. Countless well-meaning self-help books preach this gospel, as the name "self-help" implies. But this approach will take us only so far. Ultimately, it is in communion with our fellow beings and the natural world that we are made whole. We need to leave the path of Me and follow the path of We. This poetic and evocative book, drawing on the personal experiences of Good Buffalo Eagle, presents the meditations of an ancient Anasazi tribesman who rejects his family and community and walks off into the desert. During his journey, he discovers the seven paths of the Anasazi way, each path teaching a lesson symbolized by an element of the natural world: light, wind, water, stone, plants, animals, and finally the unity of all beings with the Creator, the path of We. By walking these paths, he discovers the roots of his conflict and the way toward reconciliation. For years, this book has been privately distributed by the Anasazi Foundation, an award-winning nonprofit organization whose work with troubled youth in a wilderness setting has been extraordinarily effective. But there is benefit here for all. The Seven Paths gives access to a source of wisdom and renewal familiar to native people but lost to the rest of us. As Good Buffalo Eagle writes in the foreword, this book "presents what might be described as a course in healing--seven elements among nature that combine to heal human hearts.""--
Machine generated contents note: Foreword by Good Buffalo Eagle -- 1. Beginnings -- 2. The Path of Light -- 3. The Path of Wind -- 4. The Path of Water -- 5. The Path of Stone -- 6. The Path of Plants -- 7. The Path of Animals -- 8. The Path of "We" -- 9. Destinations: Forward Walking -- About ANASAZI.
Description based on print version record.
Keywords: Indians of North America -- Religion; Indian philosophy -- North America; Mind and body; Spiritual life; BODY, MIND & SPIRIT / Inspiration & Personal Growth; SELF-HELP / Personal Growth / Happiness; SELF-HELP / Spiritual; SOCIAL SCIENCE / Ethnic Studies / Native American Studies; RELIGION / Ethnic & Tribal; Electronic books